Pronunciation Challenges Faced by Libyan EFL Leaners (Journal of Human Sciences, 2025)
Effective interaction in English requires accurate pronunciation skills, particularly in mastering consonant clusters. Understanding the specific challenges faced by learners can help educators develop targeted strategies to improve these skills.  This study investigates the pronunciation challenges encountered by Libyan university students in the English Department at Fezzan University, focusing specifically on difficulties with two-initial and three-initial consonant clusters. The research involved (13) participants and indicated that while the students displayed a commendable proficiency in pronouncing two-initial clusters—averaging 13 correct pronunciations with a low error rate of 13.3%—their performance on three-initial clusters was significantly weaker, averaging only 4.31 correct pronunciations and exhibiting an error rate of 69.2%. These results highlight the considerable difficulties associated with complex consonant combinations, which are further complicated by interference from their first language. The findings emphasize the need for targeted instructional strategies to improve pronunciation skills and enhance the overall communicative competence of Libyan learners of English.